Dynamic voltage restorer performance analysis using fuzzy logic controller and battery energy storage system for voltage sagging - Siregar, Yulianta; Azhari Nasution, Azrial Aziz; Suan Tial, Mai Kai; Mubarakah, Naemah; Soeharwinto, Soeharwinto (Institute of Advanced Engineering and Science, 2024)
Power quality is a major issue in the power transfer process. This is caused by disturbances such as voltage sags, voltage spikes, and harmonics. Voltage sag is the most common disturbance in the electric power system. However, the dynamic voltage restorer (DVR) is the most effective device for voltage sags. This research uses the DVR to overcome voltage sags using fuzzy logic controller (FLC) and battery energy storage system (BESS) to improve the performance of the DVR. The results showed that DVR using FLC improved the quality of voltage recovery compared to BESS because FLC injected a greater voltage of 0.0991 pu than BESS.